Morphological and molecular evidence of Turkish Minuartiella species (Caryophyllaceae), with a desciption of a new species and a proposal for a new combination - Koç, Murat; Hamzaoğlu, Ergin; Aksoy, Ahmet (Phytotaxa, 2019)
The genus Minuartiella comprises four species distributed in the E-Mediterranean region and SW-Asia. Some interesting specimens belonging to the genus where collected from Burdur province (Turkey). On the basis of macro- and micromprhological analyses, as well as molecular data, a new species—Minuartiella serpentinicola sp. nov.—and a new combination—Minuartiella ×antalyensis comb. nov.—are proposed in the present paper. A detailed description of the new species as well as pictures, distribution map, habitat, and IUCN category are also provided. A diagnostic key of Mnuartiella species is provided.